2022
DOI: 10.1136/jitc-2021-004452
|View full text |Cite
|
Sign up to set email alerts
|

LRIG2 promotes glioblastoma progression by modulating innate antitumor immunity through macrophage infiltration and polarization

Abstract: BackgroundGlioblastoma (GBM) is the most common malignant brain tumor with poor clinical outcomes. Immunotherapy has recently been an attractive and promising treatment of extracranial malignancies, however, most of clinical trials for GBM immunotherapy failed due to predominant accumulation of tumor-associated microglia/macrophages (TAMs).ResultsHigh level of LRIG2/soluble LRIG2 (sLRIG2) expression activates immune-related signaling pathways, which are associated with poor prognosis in GBM patients. LRIG2/sLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Notably, Li et al have shown that CD47 is expressed by human and mouse glioma cell lines and that positive cells have many characteristics of cancer stem cells [ 98 ]. The view is also supported by Hu et al [ 99 ] who report that overexpression of the LRIG2 (Leucine Rich Repeats And Immunoglobulin Like Domains 2) gene in GBM cells induces upregulation of CD47 and activation of the CD47-SIRPα anti-phagocytic axis [ 30 ]. Further experiments revealed that soluble LRIG (sLRIG) induces recruitment of BMDM that exhibit an immunosuppressive phenotype and also express high levels of CD47 receptor, SIRPα [ 99 ].…”
Section: Glioblastoma Weakens Microglia/macrophage Defence Mechanismsmentioning
confidence: 83%
See 2 more Smart Citations
“…Notably, Li et al have shown that CD47 is expressed by human and mouse glioma cell lines and that positive cells have many characteristics of cancer stem cells [ 98 ]. The view is also supported by Hu et al [ 99 ] who report that overexpression of the LRIG2 (Leucine Rich Repeats And Immunoglobulin Like Domains 2) gene in GBM cells induces upregulation of CD47 and activation of the CD47-SIRPα anti-phagocytic axis [ 30 ]. Further experiments revealed that soluble LRIG (sLRIG) induces recruitment of BMDM that exhibit an immunosuppressive phenotype and also express high levels of CD47 receptor, SIRPα [ 99 ].…”
Section: Glioblastoma Weakens Microglia/macrophage Defence Mechanismsmentioning
confidence: 83%
“…The view is also supported by Hu et al [ 99 ] who report that overexpression of the LRIG2 (Leucine Rich Repeats And Immunoglobulin Like Domains 2) gene in GBM cells induces upregulation of CD47 and activation of the CD47-SIRPα anti-phagocytic axis [ 30 ]. Further experiments revealed that soluble LRIG (sLRIG) induces recruitment of BMDM that exhibit an immunosuppressive phenotype and also express high levels of CD47 receptor, SIRPα [ 99 ]. As expected, knockdown of LRIG2 /sLRIG2 in GL261 (murine GBM) cells interferes with the activation of the CD47–SIRPα anti-phagocytic axis and enhances BMDM-mediated phagocytosis of GBM cells and suppresses GBM progression [ 99 ].…”
Section: Glioblastoma Weakens Microglia/macrophage Defence Mechanismsmentioning
confidence: 83%
See 1 more Smart Citation
“…Microglia/macrophages exhibit strong phagocytic activity. However, in glioma, the phagocytosis of GAMs is greatly reduced, due to the high expression of CD47 along with signal regulatory protein alpha (SIRPa) on the surface of GAMs ( 145 , 146 ). Therefore, a therapeutic approach involving a blockade of this signaling pathway using anti CD47 antibody to restore the phagocytic activity of GAMs has been proposed ( 145 , 146 ).…”
Section: Gams-targeted Glioma-immunotherapymentioning
confidence: 99%
“…According to the activation state of cells, TAMs can be divided into tumor-suppressing M1-like subgroup and tumor-promoting M2-like subgroup. Among them, M1-like TAMs secrete pro-inflammatory cytokines, phagocytose cancer cells to present microbial antigen to activate the adaptive immune system [7,8]. Conversely, M2-like TAMs secrete anti-inflammatory cytokines and display immunesuppressive function to promote GBM malignant behavior and tumor growth [9,10].…”
Section: Introductionmentioning
confidence: 99%